2019
DOI: 10.1016/j.jand.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the Supplemental Nutrition Assistance Program and Dietary Behaviors: Role of Community Food Environment

Abstract: Program (SNAP) is the country's largest nutrition assistance program for low-income populations. While SNAP has been shown to reduce food insecurity, research on the diet quality of program participants is inconsistent. Objective: This study examined if the community food environment is a potential moderator of the association between SNAP participation and eating behaviors. Design: This cross-sectional study utilized participant data from a telephone survey of 2,211 households in four cities in New Jersey. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…However, previous research has found that individuals who live closer to outlets that sell fresh produce consume more fruits and vegetables [37] and individuals who live in proximity to unhealthy food outlets consume fewer fruits and vegetables [38]. Living in a neighborhood with an abundance of food outlets providing unhealthy items may encourage the consumption of high calorie and low nutritional value items, like sugar-sweetened beverages, among nutrition assistance program participants [39]. Similarly, living further from supermarkets or other food outlets that sell fresh fruits and vegetables may contribute to lower consumption of produce among food assistance program participants compared to non-participating individuals [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research has found that individuals who live closer to outlets that sell fresh produce consume more fruits and vegetables [37] and individuals who live in proximity to unhealthy food outlets consume fewer fruits and vegetables [38]. Living in a neighborhood with an abundance of food outlets providing unhealthy items may encourage the consumption of high calorie and low nutritional value items, like sugar-sweetened beverages, among nutrition assistance program participants [39]. Similarly, living further from supermarkets or other food outlets that sell fresh fruits and vegetables may contribute to lower consumption of produce among food assistance program participants compared to non-participating individuals [39].…”
Section: Discussionmentioning
confidence: 99%
“…Living in a neighborhood with an abundance of food outlets providing unhealthy items may encourage the consumption of high calorie and low nutritional value items, like sugar-sweetened beverages, among nutrition assistance program participants [39]. Similarly, living further from supermarkets or other food outlets that sell fresh fruits and vegetables may contribute to lower consumption of produce among food assistance program participants compared to non-participating individuals [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, for those who are limited to food shopping near where they live, studies confirm a nearby store does improve access (350) and affordability (321). Other studies have found that decreased distance to a supermarket or grocery store improves food security, consumption of fruits and vegetables, or redemption of benefits, but increased purchase of unhealthy foods and beverages has also been observed (108,(351)(352)(353)(354). Even if physical proximity is at best weakly related to diet quality, decreasing distance could reduce disparities in the time burden to acquire food and disproportionately benefit people with disabilities and other mobility limitations who largely need or prefer to shop nearby (355).…”
Section: Physical Accessmentioning
confidence: 99%